Influence of Cardiopulmonary Bypass on the Interaction of Recombinant Factor VIIa with Activated Platelets - Kjalke, Marianne (J Extra Corpor Technol, 2009)
Recombinant factor VIIa (rFVIIa) interacts preferentially with coated platelets characterized by a high exposure of phosphatidyl serine (PS), FV, FVIII, FIX, and FX binding, and fibrinogen. Cardiopulmonary bypass (CPB) is known to impair platelet function. In this study, the influence of CPB on formation of coated platelets and the interaction of rFVIIa with the platelets were studied. Blood was either exposed to a closed CPB circuit or obtained from patients undergoing CPB-assisted cardiac surgery, and platelets were analyzed by flow cytometry with and without dual agonist stimulation with thrombin and a GPVI collagen receptor agonist known to induce coated platelet formation. Platelets circulated within a closed CPB circuit did not spontaneously form coated platelets. Dual agonists stimulation caused formation of coated platelets at a reduced level compared to pre-CPB level (51 ± 21% vs. 80 ± 17% before CPB, p < .001). The rFVIIa interaction with the coated platelets was not impaired after CPB. Platelets isolated from patients undergoing CPB-assisted cardiac surgery also formed coated platelets only after dual agonist stimulation but to the same level as before surgery (76 ± 8% vs. 83 ± 14% before surgery, p = .17, n = 10). rFVIIa interaction with the coated platelets was not impaired after surgery. No spontaneous rFVIIa-binding platelets were found. The data indicate that CPB exposure in vivo does not compromise the platelet-dependent effects of rFVIIa either by spontaneous formation of coated platelets, thereby limiting the risk of systemic coagulation, or by impairing rFVIIa interaction with the agonist-induced coated platelets, thereby retaining the hemostatic potential of rFVIIa after CPB.